2023
DOI: 10.1371/journal.pone.0291745
|View full text |Cite
|
Sign up to set email alerts
|

The impact of deep learning reconstruction in low dose computed tomography on the evaluation of interstitial lung disease

Chu hyun Kim,
Myung Jin Chung,
Yoon Ki Cha
et al.

Abstract: To evaluate the effect of the deep learning model reconstruction (DLM) method in terms of image quality and diagnostic agreement in low-dose computed tomography (LDCT) for interstitial lung disease (ILD), 193 patients who underwent LDCT for suspected ILD were retrospectively reviewed. Datasets were reconstructed using filtered back projection (FBP), adaptive statistical iterative reconstruction Veo (ASiR-V), and DLM. For image quality analysis, the signal, noise, signal-to-noise ratio (SNR), blind/referenceles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“… 31 , 37 39 Another 4 studies done with LD chest CT with DLIR [CTDI vol (1.07-2.38 mGy.cm), DLP (79.69-08.7 mGy.cm), SSDE (0.69-1.07 mGy), ED (0.98-1.03 mSv)]. 30 , 32 , 34 , 35 One study done with Quarter low dose (QLD) CT Chest using DLIR showed 75% reduction in radiation dose compared to IR. 33 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 31 , 37 39 Another 4 studies done with LD chest CT with DLIR [CTDI vol (1.07-2.38 mGy.cm), DLP (79.69-08.7 mGy.cm), SSDE (0.69-1.07 mGy), ED (0.98-1.03 mSv)]. 30 , 32 , 34 , 35 One study done with Quarter low dose (QLD) CT Chest using DLIR showed 75% reduction in radiation dose compared to IR. 33 …”
Section: Resultsmentioning
confidence: 99%
“…29 CT chest examination: A total of nine studies from chest CT that used DLIR showed a reduction in IN (9-50%) compared with IR and FBP. [30][31][32][33][34][35][36][37][38][39] Four studies compared LD with DLIR and SD with IR for chest CT and observed a reduction (62-97%) in RD. 30,32,34,35 One study done with Quarter low dose (QLD) CT Chest using DLIR showed 75% reduction in radiation dose compared to IR.…”
Section: Image Noise (In) and Radiation Dose (Rd) Reduction In Ct Hea...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some studies accessed the quality of denoised medical images by relying on IQA metrics from the natural image processing domain [ 18 , 19 , 20 ]. These metrics fall into two categories: full-reference IQA (FR-IQA) and non-reference IQA (NR-IQA).…”
Section: Introductionmentioning
confidence: 99%